Integrating meta-analysis and experts’ knowledge for prioritizing climate-smart agricultural practices in Ethiopian - Adimassu, Zenebe; Tibebe, Degefie; Abera, Wuletawu; Tamene, Lulseged D. (Elsevier, 2024)
Various climate-smart agricultural (CSA) practices are being advocated in different agroecological zones of Ethiopia to enhance the sustainability, resilience, and productivity of the agricultural sector in response to climate change. Prioritizing and packaging these CSA practices are essential to amplify the impact of climate change mitigation efforts. By strategically selecting and prioritizing these practices and technologies, resources can be allocated effectively to activities with the highest potential for reducing greenhouse gas emissions, bolstering resilience, and fostering sustainable development. However, identifying and prioritizing climate-smart practices that cater to the needs of vulnerable farmers and are tailored to specific local contexts remains challenging, often hindered by subjective assessments and limited awareness. The objective of this paper was to enhance the precision and objectivity of prioritizing CSA practices by leveraging a combination of research findings and expert knowledge. The steps included the following: i) a CSA prioritization assessment framework was used to identify and prioritize CSA practices across various agro-ecologies based on the CSA pillars (productivity, adaptation, and mitigation); ii), a meta-analysis approach was employed to determine the effect size of various CSA practices on the three pillars of CSA practices; iii), the effect size values were rescaled and ranked based on effect size categories; and iv), correlation was performed to assess the relationship between the two approaches, and finally, average values were taken to integrate and determine the final rank of CSA practices. Overall, we found out that there were weak correlations between the ranks of the two approaches, resulted in a mismatch between the ranks of CSA practices by experts and meta-analysis results. Using the meta-analysis approach, only 35% of the CSA practices were equally ranked by both approaches, 40% of the CSA practices were more likely ranked by experts, while 25% of the CSA practices were more likely ranked by the meta-analysis approach. This implies that experts overestimated the effect of various CSA practices on various indicators of productivity, soil loss, and run-off and soil organic matter. Integrating the ranks of the two approaches helped to target CSA practices across various agro-ecological zones. According to the combined ranking, several CSA practices were targeted to six major agro-ecological zones in the country. These various CSA practices increase productivity, enhance adaptation, and sequester carbon dioxide from the atmosphere. Based on the availability of these CSA practices, it is possible to package various combinations of these practices.